Flexibility from Combined Heat and Power: A Techno-Economic Study for Fully Renewable Åland Islands - Tomi Thomasson; Kirsikka Kiviranta; Antton Tapani; Matti Tähtinen (Energies, 2021)
As energy systems globally are transitioning into renewable energy, simultaneous targets of high self-sufficiency have led to complex system design proposals. While conventional technology solutions would reduce the complexity in theory, limitations in the potential outcome may exist. To address this dilemma, the work quantified the systemic value provided by a conventional solution; biomass combined heat and power (CHP) production, in terms of economic feasibility, provided flexibility and energy self-sufficiency. The analysis focused on the renewable energy integration of the Åland Islands, where the synergetic island energy system is heavily increasing the wind power capacity. While considering local fuel resource availability, multiple alternative energy system scenarios were constructed. To evaluate the scenarios, the work developed and validated a combined dispatch and investment optimization model. The results showed that the studied conventional approaches limited the achievable self-sufficiency in the power sector (80.6%), however, considerably increasing the value from the present state (18.5%). Second, compared to previous studies, the results indicated a low value from biomass CHP in the wind-based energy system. Instead, the combination of high wind capacity and power-to-heat enabled the best economic feasibility and high self-sufficiency, which could be further improved by lower electricity taxation.